Calcitriol Ameliorates Kidney Injury Through Reducing Podocytopathy, Tubular Injury, Inflammation and Fibrosis in 5/6 Subtotal Nephrectomy Model in Rats - SARI, DWI CAHYANI RATNA (Kobe J Med Sci, 2020)
Chronic kidney diseases (CKDs) lead to end-stage renal diseases (ESRD) which are characterized by glomerulosclerosis, tubular injury, anemia, inflammation, and interstitial fibrosis. Vitamin D is known to have renal protective effects. However, its effects relate to low and high doses of Vitamin D in CKD model is still unknown. CKD was performed using 5/6 subtotal nephrectomy procedure in male Sprague Dawley rats (3 months old, 200–300 grams, SN group; n=6), then rats were sacrificed on day 14 after operation. Sham operation was used for control (SO group; n=6). Calcitriol was administered in two doses : 0.01 μg/mL/100 gramsBW/day (SND1 group; n=6) and 0.05 μg/mL/100 gramsBW/day (SND2 group; n=6) intraperitoneally for 14 days. Glomerulosclerosis and tubular injury score were examined using PAS staining, meanwhile, interstitial fibrosis area fraction was assessed with Sirius Red staining. RT-PCR was performed for assessing nephrin, podocin, IL-6, CD68, Collagen-1, and TGF-β1 mRNA expressions. Immunostaining (IHC) was carried out to observe macrophage (CD68) and myofibroblast (α-SMA). SN demonstrated CKD condition with higher tubular injury, glomerulosclerosis, interstitial fibrosis, and inflammation compared to SO. Calcitriol-treated group (especially SND2) demonstrated significant lower tubular injury, glomerulosclerosis, and interstitial fibrosis compared to SN. SND2 group showed not only significantly lower CD68, IL-6, Collagen-1, and TGF-β1 mRNA expressions, but also higher mRNA expressions of nephrin and podocin. SND2 group also demonstrated reduction of macrophages infiltration and myofibroblasts expansion based on its histopathological appearance. Vitamin D may have a renoprotective effect on 5/6 subtotal nephrectomy model by attenuating podocytopathy, tubular injury, inflammation and interstitial fibrosis.